Process Optimization in Micro, Small and Medium-sized Enterprises (MSMEs) in the Apparel Industry: A Case Study Integrating Predetermined Time Techniques and Technology - Bermúdez Monsalve, José Martín
The textile industry, crucial for Colombia's economic growth, accounted for 9.4% of the GDP in 2022, benefiting from the Asian market's challenges due to the pandemic and encouraging local production (La República, 2023). However, 2023 presents notable challenges such as changes in labor legislation, tariff increases, and a slowdown in national production and fashion spending, affected by inflation that has diminished the purchasing power of Colombian households. In this context, predetermined time measurement becomes even more important due to current legislation reducing the workday without lowering wages, thus maintaining efficient and competitive production. Previous research has shown that these predetermined time techniques are essential for obtaining reliable standard times, enabling companies to determine accurate rates, control labor efficiency, plan personnel and machinery needs, balance production lines, and reduce overall production times. This article results from applied research conducted in three small and medium-sized garment businesses in Medellín, implementing a predetermined time simulator, micro-motion tables based on MTM, and templates for balancing the garment production process, along with stopwatch time sheets.